Educational psychology - Sternberg, Robert J.; Williams, Wendy M. [ (Wendy Melissa)] , 1960- (Merrill, 2010)
"Written to help readers understand and develop expertise in both teaching and learning, Educational Psychology focuses on the art and science necessary to become an expert teacher. Renowned scholars Sternberg and Williams help readers capitalize on their strengths by integrating questions into the text that encourage analytical, creative, and practical thinking. This framework, based on Sternberg's triarchic theory of human intelligence, helps ensure that readers think deeply about what they are learning, rather than merely processing information at a superficial level."--BOOK JACKET.